2019
DOI: 10.1371/journal.pone.0221430
|View full text |Cite
|
Sign up to set email alerts
|

Intensity, frequency, duration, and volume of physical activity and its association with risk of depression in middle- and older-aged Chinese: Evidence from the China Health and Retirement Longitudinal Study, 2015

Abstract: Background The general benefit of physical activity (PA) to one’s mental health has been widely acknowledged. Nevertheless, the specific type and amount of PA that associates with lower risk of depression in China awaits further investigation. The present study was conducted on middle- and older-aged Chinese population with two objectives: 1) to understand the patterns of PA; 2) to measure the associations between depression and PA at different levels from various aspects. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 59 publications
2
38
1
3
Order By: Relevance
“…Previous evidence indicates that there is comorbidity between depression and some chronic diseases such as diabetes, hypertension, and cardiovascular problems (Chireh et al, 2019;Naveen et al, 2020;Rotella & Mannucci, 2013;Seldenrijk et al, 2015;Vancampfort et al, 2016;Wang et al, 2019), which is consistent with the findings found in the present investigation, since, when analyzing the effect that the type of condition had on depressive symptoms, the results indicated that older adults (specifically women) with both diabetes and hypertension were the ones who presented the most depressive symptoms. There are studies (Boulé et al, 2005;Musen et al, 2008) suggesting a relationship between diabetes and depressive symptoms, this due to the fact that high glucose levels increase the levels of brain neurotransmitters associated with an elevated risk of depressive symptoms.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Previous evidence indicates that there is comorbidity between depression and some chronic diseases such as diabetes, hypertension, and cardiovascular problems (Chireh et al, 2019;Naveen et al, 2020;Rotella & Mannucci, 2013;Seldenrijk et al, 2015;Vancampfort et al, 2016;Wang et al, 2019), which is consistent with the findings found in the present investigation, since, when analyzing the effect that the type of condition had on depressive symptoms, the results indicated that older adults (specifically women) with both diabetes and hypertension were the ones who presented the most depressive symptoms. There are studies (Boulé et al, 2005;Musen et al, 2008) suggesting a relationship between diabetes and depressive symptoms, this due to the fact that high glucose levels increase the levels of brain neurotransmitters associated with an elevated risk of depressive symptoms.…”
Section: Discussionsupporting
confidence: 93%
“…With reference to the effect of sex, age, and medical condition (hypertension and/or diabetes) on the psychological factors evaluated in the situation of the COVID-19 pandemic, the results of the present study showed that it is women who present the highest depression symptoms, and anxiety and who perceive a greater impact due to the situation of the pandemic in contrast to men, which agrees with previous literature (Naveen et al, 2020;World Health Organization, 2017;Reddy et al, 2012;Wang et al, 2019) In relation to how much depression like anxiety, are ailments that occur more frequently in women than in men. Likewise, previous studies indicate that age is also a factor that may increase the probability of presenting depressive symptoms, which is consistent with the findings of the present study, where older women (80 years or older) were those who presented higher scores.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Prior findings regarding the gender-disparity in the relationship between SP and mental health are competing, as some reporting favourable effects only in women [ 40 ] or only in men [ 41 ], whereas some observed no gender differences [ 42 ]. The present study observed similar patterns in gender subgroups, and thus suggested that encouraging sufficient SP may be equally beneficial to men and women in China’s context.…”
Section: Discussionmentioning
confidence: 99%